Answer:
<h3>For two events A and B show that P (A∩B) ≥ P (A)+P (B)−1.</h3>
By De morgan's law
![(A\cap B)^{c}=A^{c}\cup B^{c}\\\\P((A\cap B)^{c})=P(A^{c}\cup B^{c})\leq P(A^{c})+P(B^{c}) \\\\1-P(A\cap B)\leq P(A^{c})+P(B^{c}) \\\\1-P(A\cap B)\leq 1-P(A)+1-P(B)\\\\-P(A\cap B)\leq 1-P(A)-P(B)\\\\P(A\cap B)\geq P(A)+P(B)-1](https://tex.z-dn.net/?f=%28A%5Ccap%20B%29%5E%7Bc%7D%3DA%5E%7Bc%7D%5Ccup%20B%5E%7Bc%7D%5C%5C%5C%5CP%28%28A%5Ccap%20B%29%5E%7Bc%7D%29%3DP%28A%5E%7Bc%7D%5Ccup%20B%5E%7Bc%7D%29%5Cleq%20P%28A%5E%7Bc%7D%29%2BP%28B%5E%7Bc%7D%29%20%5C%5C%5C%5C1-P%28A%5Ccap%20B%29%5Cleq%20%20P%28A%5E%7Bc%7D%29%2BP%28B%5E%7Bc%7D%29%20%5C%5C%5C%5C1-P%28A%5Ccap%20B%29%5Cleq%20%201-P%28A%29%2B1-P%28B%29%5C%5C%5C%5C-P%28A%5Ccap%20B%29%5Cleq%20%201-P%28A%29-P%28B%29%5C%5C%5C%5CP%28A%5Ccap%20B%29%5Cgeq%20P%28A%29%2BP%28B%29-1)
which is Bonferroni’s inequality
<h3>Result 1: P (Ac) = 1 − P(A)</h3>
Proof
If S is universal set then
![A\cup A^{c}=S\\\\P(A\cup A^{c})=P(S)\\\\P(A)+P(A^{c})=1\\\\P(A^{c})=1-P(A)](https://tex.z-dn.net/?f=A%5Ccup%20A%5E%7Bc%7D%3DS%5C%5C%5C%5CP%28A%5Ccup%20A%5E%7Bc%7D%29%3DP%28S%29%5C%5C%5C%5CP%28A%29%2BP%28A%5E%7Bc%7D%29%3D1%5C%5C%5C%5CP%28A%5E%7Bc%7D%29%3D1-P%28A%29)
<h3>Result 2 : For any two events A and B, P (A∪B) = P (A)+P (B)−P (A∩B) and P(A) ≥ P(B)</h3>
Proof:
If S is a universal set then:
![A\cup(B\cap A^{c})=(A\cup B) \cap (A\cup A^{c})\\=(A\cup B) \cap S\\A\cup(B\cap A^{c})=(A\cup B)](https://tex.z-dn.net/?f=A%5Ccup%28B%5Ccap%20A%5E%7Bc%7D%29%3D%28A%5Ccup%20B%29%20%5Ccap%20%28A%5Ccup%20A%5E%7Bc%7D%29%5C%5C%3D%28A%5Ccup%20B%29%20%5Ccap%20S%5C%5CA%5Ccup%28B%5Ccap%20A%5E%7Bc%7D%29%3D%28A%5Ccup%20B%29)
Which show A∪B can be expressed as union of two disjoint sets.
If A and (B∩Ac) are two disjoint sets then
B can be expressed as:
![B=B\cap(A\cup A^{c})\\](https://tex.z-dn.net/?f=B%3DB%5Ccap%28A%5Ccup%20A%5E%7Bc%7D%29%5C%5C)
If B is intersection of two disjoint sets then
![P(B)=P(B\cap(A)+P(B\cup A^{c})\\P(B\cup A^{c}=P(B)-P(B\cap A)](https://tex.z-dn.net/?f=P%28B%29%3DP%28B%5Ccap%28A%29%2BP%28B%5Ccup%20A%5E%7Bc%7D%29%5C%5CP%28B%5Ccup%20A%5E%7Bc%7D%3DP%28B%29-P%28B%5Ccap%20A%29)
Then (1) becomes
![P(A\cup B) =P(A) +P(B)-P(A\cap B)\\](https://tex.z-dn.net/?f=P%28A%5Ccup%20B%29%20%3DP%28A%29%20%2BP%28B%29-P%28A%5Ccap%20B%29%5C%5C)
<h3>Result 3: For any two events A and B, P(A) = P(A ∩ B) + P (A ∩ Bc)</h3>
Proof:
If A and B are two disjoint sets then
![A=A\cap(B\cup B^{c})\\A=(A\cap B) \cup (A\cap B^{c})\\P(A)=P(A\cap B) + P(A\cap B^{c})\\](https://tex.z-dn.net/?f=A%3DA%5Ccap%28B%5Ccup%20B%5E%7Bc%7D%29%5C%5CA%3D%28A%5Ccap%20B%29%20%5Ccup%20%28A%5Ccap%20B%5E%7Bc%7D%29%5C%5CP%28A%29%3DP%28A%5Ccap%20B%29%20%2B%20P%28A%5Ccap%20B%5E%7Bc%7D%29%5C%5C)
<h3>Result 4: If B ⊂ A, then A∩B = B. Therefore P (A)−P (B) = P (A ∩ Bc) </h3>
Proof:
If B is subset of A then all elements of B lie in A so A ∩ B =B
where A and A ∩ Bc are disjoint.
![P(A)=P(B\cup ( A\cap B^{c}))\\\\P(A)=P(B)+P( A\cap B^{c})](https://tex.z-dn.net/?f=P%28A%29%3DP%28B%5Ccup%20%28%20A%5Ccap%20B%5E%7Bc%7D%29%29%5C%5C%5C%5CP%28A%29%3DP%28B%29%2BP%28%20A%5Ccap%20B%5E%7Bc%7D%29)
From axiom P(E)≥0
![P( A\cap B^{c})\geq 0\\\\P(A)-P(B)=P( A\cap B^{c})\\P(A)=P(B)+P(A\cap B^{c})\geq P(B)](https://tex.z-dn.net/?f=P%28%20A%5Ccap%20B%5E%7Bc%7D%29%5Cgeq%200%5C%5C%5C%5CP%28A%29-P%28B%29%3DP%28%20A%5Ccap%20B%5E%7Bc%7D%29%5C%5CP%28A%29%3DP%28B%29%2BP%28A%5Ccap%20B%5E%7Bc%7D%29%5Cgeq%20P%28B%29)
Therefore,
P(A)≥P(B)
So 5x=30
then x= 30/5
and x=6
so the answer is last one !
H(x) = 125^x
Domain: all the real numbers (from negative infinity to infinity)
Range: all the positive real numbers.
As x decreases 125^x decreases approaching to 0. The function will never reach the value 0 but will approximate to it as x goes to negative infinity. The rate of decreasing gets lower and lower, with a limit of zero, when x becomes more and more negative.
As x increases 125^x increases indefinetely and at an increasing rate. That means that the increase is accelerated (the bigger the value of x the bigger the rate of increasing).
Answer:
![y = -3x+11](https://tex.z-dn.net/?f=y%20%3D%20-3x%2B11)
Step-by-step explanation:
I accept your challenge!
First we know that a equation of the line is a linear equation, and its equation is:
![y = mx+b](https://tex.z-dn.net/?f=y%20%3D%20mx%2Bb)
![m: \text{slope}\\b: \text{y-intercept}](https://tex.z-dn.net/?f=m%3A%20%5Ctext%7Bslope%7D%5C%5Cb%3A%20%5Ctext%7By-intercept%7D)
In this context, the slope, defined as the steepness of a line is characterized as the ratio of RISE (the difference in the y-coordinates, the vertical change) over the RUN (the difference in x-coordinates, the horizontal change).
![$m=\frac{\text{change in y}}{\text{change in x}}=\frac{\Delta y}{\Delta x}=\frac{y_{2}-y_{1}}{x_{2}-x_{1}} $](https://tex.z-dn.net/?f=%24m%3D%5Cfrac%7B%5Ctext%7Bchange%20in%20y%7D%7D%7B%5Ctext%7Bchange%20in%20x%7D%7D%3D%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%20%20%20%24)
Once we know two points where the line goes through, we can get the slope, once we know the change in y and x.
I will take
as Point 1 and
as Point 2.
So, ![x_{1}=3 \text{ and } y_{1}=2\\x_{2}=4 \text{ and } y_{2}=-1](https://tex.z-dn.net/?f=x_%7B1%7D%3D3%20%5Ctext%7B%20and%20%7D%20y_%7B1%7D%3D2%5C%5Cx_%7B2%7D%3D4%20%5Ctext%7B%20and%20%7D%20y_%7B2%7D%3D-1)
![$m=\frac{\text{change in y}}{\text{change in x}}=\frac{\Delta y}{\Delta x}=\frac{-1-2}{4-3} $](https://tex.z-dn.net/?f=%24m%3D%5Cfrac%7B%5Ctext%7Bchange%20in%20y%7D%7D%7B%5Ctext%7Bchange%20in%20x%7D%7D%3D%5Cfrac%7B%5CDelta%20y%7D%7B%5CDelta%20x%7D%3D%5Cfrac%7B-1-2%7D%7B4-3%7D%20%20%20%24)
![$m=\frac{-3}{1}=-3 $](https://tex.z-dn.net/?f=%24m%3D%5Cfrac%7B-3%7D%7B1%7D%3D-3%20%24)
Now we have to find the y-intercept:
To do so, think about the the points given and the nearly finished equation, we can find b with those two informations.
Our currently equation of the line is:
![y = -3x+b](https://tex.z-dn.net/?f=y%20%3D%20-3x%2Bb)
Using the points, take Point 1 as an example, it says that when
, so plugging it in the equation:
![2 = -3(3)+b\\2 = -9+b\\11 = b](https://tex.z-dn.net/?f=2%20%3D%20-3%283%29%2Bb%5C%5C2%20%3D%20-9%2Bb%5C%5C11%20%3D%20b)
Taking the Point 2
![-1 = -3(4)+b\\-1 = -12+b\\11 = b](https://tex.z-dn.net/?f=-1%20%3D%20-3%284%29%2Bb%5C%5C-1%20%3D%20-12%2Bb%5C%5C11%20%3D%20b)
Now we found
! The equation is complete!
![y = -3x+11](https://tex.z-dn.net/?f=y%20%3D%20-3x%2B11)
The tie was marked down by 40%